If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(u + -5) + -8u = 0 Reorder the terms: 4(-5 + u) + -8u = 0 (-5 * 4 + u * 4) + -8u = 0 (-20 + 4u) + -8u = 0 Combine like terms: 4u + -8u = -4u -20 + -4u = 0 Solving -20 + -4u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -4u = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -4u = 0 + 20 -4u = 0 + 20 Combine like terms: 0 + 20 = 20 -4u = 20 Divide each side by '-4'. u = -5 Simplifying u = -5
| Cy=ax+b | | -6p-4=-3+2 | | 3(n+5)-6=#n+9 | | 9x+11x+2=0 | | 2(2-3y)+6y=5 | | -3x+9=-3x+3 | | (12+x)2=8 | | -3s=2 | | y-(-5)=(6/7)(x-3) | | -132=6(-3n+2) | | 6-9p+4p= | | -3(x-8)-5=9(x+2)11 | | 99=-m+8(8+m) | | a/6=6 | | 3z=90 | | y-(-8)=(6/7)(x-5) | | 3x/5-3x/5-7 | | -7.2=1.3n-0.3n-1.0 | | 5(2x+4)+3(2x-2)=24 | | x-.50x=43 | | (y+1)+1=3y | | f-g=3g | | 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= |